Plant Survival of Drought During Establishment: An Interspecific Comparison of Five Grain Legumes. Issue 3 (1st May 2015) - Marrou, Helene; Vadez, Vincent; Sinclair, Thomas R.
ABSTRACT: Seedling establishment is obviously the first step in having successful crop production. In seasons and locations that experience early drought, potential differences among species in plant survival of drought could result in greater probability of crop establishment. In this study, plant survival capacity during crop establishment was tested for five grain legume species: soybean [ Glycine max (L.) Merr.], common bean ( Phaseolus vulgaris L.), groundnut ( Arachis hypogaea L.), cowpea ( Vigna unguiculata L. Walp.), and pigeon pea ( Cajanus cajan L. Huth). Experiments were done for four sowing conditions (two soil textures × two initial soil‐water contents). Cowpea and pigeon pea had the greatest capacity for survival, while soybean, bean, and groundnut were more sensitive. Differences among species could not be explained by differences in the temporal dynamics of water use. Conversely, plant wilting and senescence in response to soil dehydration varied among species; initial wilting of cowpea and pigeon pea occurred at lower soil‐water contents. These two species also had the longest survival after fraction transpirable soil water (FTSW) reached zero. In a comparison of 10 genotypes of each species, genotypic variation in the wilting profile during the survival phase was observed in cowpea, bean, and, to a lesser extent, groundnut and pigeon pea, but no differences were found in soybean.